DOI: 10.4995/thesis/10251/153164
|View full text |Cite
|
Sign up to set email alerts
|

A causal model to explain data reuse in science: a study in health disciplines

Abstract: and Areti Angeliki Veroniki (PhD). Thanks for all your time answering my questions during the interviews and for responding my emails. Without you, this dissertation would not exist.Second, I want to thanks my three PhD advisors for their intellectual and emotional support. Their different backgrounds have enriched my learning process, and contributed to the completion of this dissertation in varied ways. Choices and imperfections in this dissertation are my own. Thanks also to Ian Graham (PhD) and Sylvie Gros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 138 publications
(246 reference statements)
0
0
0
Order By: Relevance
“…It may be that the degree to which survey respondents experienced data scarcity was not enough to limit their opportunities to engage with and build trust in data repositories. This aligns with previous findings by Borrás (2020) who investigated the underlying mechanisms for data reuse. She found that researchers reused data even when they had a less than an optimal amount.…”
Section: Discussionsupporting
confidence: 92%
“…It may be that the degree to which survey respondents experienced data scarcity was not enough to limit their opportunities to engage with and build trust in data repositories. This aligns with previous findings by Borrás (2020) who investigated the underlying mechanisms for data reuse. She found that researchers reused data even when they had a less than an optimal amount.…”
Section: Discussionsupporting
confidence: 92%